Help! I'm an author - get me out of here. A wish list for better research dissemination - Rumsey, S (2017)
The current UK open access (OA) environment is extremely complex, and the concept of OA as a ‘good thing’ is being lost. Inefficient processes are unavoidable; an astonishing amount of money is changing hands; numerous new journals are being produced; OA policies and funding are regularly reviewed and open to change; and all the while, research dissemination is evolving. Authors are caught in the middle of a complicated, and sometimes conflicting, mixture of requirements from funders and publishers. Many researchers want to use new models to distribute their findings and discuss them with peers. University research support staff attempt to filter policy requirements and simplify instructions and procedures for authors, whilst supporting them in using all forms of dissemination. This presentation focuses on the difficulties encountered when managing OA support for researchers within a large research-intensive institution, and challenges publishers with a wish list.